2012
DOI: 10.1016/j.bbadis.2011.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminus of PARK2 is required for its self-interaction, solubility and role in the spindle assembly checkpoint

Abstract: PARK2, an ubiquitin ligase closely correlated with Parkinson's disease and cancer, has been shown to accumulate at centrosomes to ubiquitinate misfolded proteins accumulated during interphase. In the present study, we demonstrated that PARK2 can also localize to centrosomes in mitosis and that the protein does not fluctuate through the S- to M-phase. A C-terminal truncation of PARK2 resulted in a spindle assembly checkpoint defect, characterized by HeLa cells able to bypass mitotic arrest induced by nocodazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…To understand the molecular mechanisms underlying the role of parkin in pancreatic cancer, we analyzed its subcellular localization during the cell cycle. Consistent with previous findings, 25,26 we found that in interephase cells parkin had punctate distribution in the cytosol and prominent accumulation in the perinuclear region (Fig. 4A).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…To understand the molecular mechanisms underlying the role of parkin in pancreatic cancer, we analyzed its subcellular localization during the cell cycle. Consistent with previous findings, 25,26 we found that in interephase cells parkin had punctate distribution in the cytosol and prominent accumulation in the perinuclear region (Fig. 4A).…”
Section: Resultssupporting
confidence: 93%
“…26 In addition, parkin has been implicated in the spindle assembly checkpoint, although the molecular details remain to be uncovered. 25 In the present study, our data reveal that in mitosis, parkin is mainly localized at the spindle poles, with modest distribution at the central spindle and the midbody. Consistent with the localization pattern of parkin, silencing of its expression results in a remarkable increase in the percentage of cells with metastasize and therapeutic resistance.…”
Section: Discussionsupporting
confidence: 59%
“…11 A C-terminal truncation of parkin results in a spindle assembly checkpoint defect in the S-to M-phase. 21 Parkin may inhibit the growth of human cervical cancer cells by decreasing the 40S ribosomal protein SA (RPSA) expression and inducing phosphorylation of cytokeratin 8/18. 22 Parkin, as a novel component in the p53 tumor suppression pathway, contributes to the functions of p53 in regulating energy metabolism, especially the Warburg effect, and antioxidant defense.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the localization of Park2 protein at microtubules is an important factor for its ubiquitin ligase activity toward misfolded substrates. Park5 or UCHL1 gene provides instruction to produce ubiquitin carboxyl-terminal esterase L1 enzyme, and UCHL1 is a member of deubiquitylating enzymes (DUBs) that reverse the action of ubiquitylation reactions in ubiquitin-proteosome pathway (Chen et al 2012;Kahle et al 2009). Park7 mRNA or also known as of DJ-1 gene is a ubiquitous redoxresponsive neuroprotective protein with diverse functions.…”
Section: Discussionmentioning
confidence: 99%